Pemberdayaan Masyarakat Oleh Mahasiswa melalui Pemanfaatan Potensi Lokal Desa Mayayap Kecamatan Bualemo Kabupaten Banggai - Fitriani Fitriani; Yanti Mutalib; Moh Muchlis Djibran (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program (KKN PMM) conducted by students in Mayayap Village, Bualemo District, Banggai Regency, aimed to increase the added value of local agricultural and fishery products. Partners faced several obstacles, including limited skills in processing available local resources, such as coconuts, bananas, fish, shrimp, and crab; limited business capital; poor packaging techniques; and weak marketing management. Activities included outreach, production training, improved packaging techniques, marketing strategies, business management, and the provision of production equipment. The program resulted in the development of five superior village products: fish floss, shrimp nuggets, crab crackers, Virgin Coconut Oil (VCO), and banana chips. Furthermore, partners experienced improved skills in production, business management, and marketing. This program supports the achievement of the Sustainable Development Goals (SDGs), specifically poverty alleviation, women's empowerment, and food and economic security. Outputs included the publication of scientific articles, online media coverage, posters, and video documentation. Collaboration between universities and the community has been proven to strengthen the village economy sustainably.